Tingkat Pemahaman Konsep dan Motivasi Siswa dengan Penerapan Multimedia Berbasis Model SAVI dalam Pembelajaran Karakteristik Gelombang di Kelas XI SMA - Karwanti Karwanti; M. Rahmad; Azizahwati Azizahwati (Edusainstika: Jurnal Pembelajaran MIPA, 2023)
There is still low motivation and understanding of students' concepts, especially in learning wave characteristics for class XI SMA 1 Bandar Sei Kijang students, making this problem important to research. The purpose of this research was to determine the level of conceptual understanding and motivation of class XI students through the application of PowerPoint learning multimedia based on the SAVI model. This type of quantitative research uses a quasi-experimental method, using a pretest-posttest control group design. The research sample was taken from the XI MIPA class population of 42 students. The research instrument consisted of a concept understanding test of 5 indicators (20 objective questions) and a motivational questionnaire with 4 aspects (25 statements). Data were analyzed descriptively and inferential analysis using parametric statistics, related to the level of understanding of the concept and the learning motivation of the participants. The results of the descriptive analysis obtained that the understanding of the concept in the experimental class increased with a score of 75.9% and learning motivation increased with a score of 70.5% (good category). The results of the inferential analysis with the t-test obtained a significant increase in conceptual understanding and student motivation. There is a relationship between the level of understanding of the concept and the increase in participant motivation. So the implementation of SAVI-based PowerPoint learning multimedia on wave characteristic material is effective in increasing students' conceptual understanding and motivation in class XI SMA.